MSMEs Debt Financing Decisions in West Sumatera, Indonesia During Covid-19 Pandemic: MSMEs Debt Financing Decisions in West Sumatera, Indonesia During Covid-19 Pandemic - suryani, indah permata (Jurnal Akuntansi dan Governance Andalas, 2021)
This Paper develops an empirical taxonomy of debt Financing Decisions of MSMES In Padang City by performing a cluster analysis including This literature has shown that one of the problems that often become an obstacle to the development of micro, small, and medium enterprises (SMEs) is very difficult to get access to finance and capital. Eventhough there are several scheme offered by Government to support MSMEs during Pandemi, in the practice for the rural areas. The objective might be not successful. This study will shed the light type of debt financing decisions implement by MSMEs in Padang During pandemic Covid-19. Furthermore, the SME financing can be categorized based on type of the firm including size and profitability. This study is to focusing which type of debt financing decision is utilized by MS in West Sumatera During covid-19 pandemic especially related to bank loans and other schemes provided. To do this MSMEs data from certain Communities in West Sumatera are used. The collecting data process was obtained through online questionnaires distributed to more than 100 MSMEs. The findings from the survey show that the legal type size of the firm influence the decision to apply for debt financing but the age of MSMEs do not affect by the debt financing decision used by MSMEs. Keywords: Debt Financing, Access to Finance, Micro and Small Medium Entreprises